Agrotourisme durable au Sénégal : Cartographie et enjeux socio-économiques - Massamba Souleymane Seck; Sylvie Kahoumane Assine; Abdoukhadre Sow (Études Caribéennes)
This article analyzes the importance of sustainable agrotourism in Senegal. Through exploratory research, we were able to map existing agrotourism farms in Senegal and highlight their socio-economic challenges. The results of this research show that the development of agrotourism farms contributes to improving the quality of the offerings, intensifying tourism promotion, and the investments made to boost this sector. However, sustainable agrotourism appears to adopt a participatory development model to meet the diverse needs of the areas served, particularly rural and remote areas, and also contributes to the training and supervision of youth and the farming population. With this in mind, the practice of agrotourism aims to conserve the environment and promote the efficient use of ecological resources. Such a practice also highlights the sustainable development aspect of the Senegalese tourism sector.